IMPACT OF METHANOLIC EXTRACT OF PEGANUM HARMALA ON THE WEIGHT GAIN, FEED CONVERSION RATIO, FEED COST AND GROSS RETURN OF BROILER CHICKS - A. J. Tanweer; N. Chand; S. Khan; M. S. Qureshi; A. Akhtar; M. Niamatullah (Journal of Animal and Plant Sciences, 2012)
The present study was carried out to explore the potential of Peganum harmala (P.harmala) methanolic extract on the weight gain, feed conversion ratio, feed cost and gross return of broiler chicks. For this purpose, 120 seven days old chicks of approximately same weight were used. The chicks were divided into four treatment groups; Ph-0, Ph-200, Ph-250 and Ph-300 receiving methanolic extract of P. harmala at the rate of 0, 200, 250 and 300 mg/L of drinking water respectively.  Each group was replicated 3 times having 10 chicks per replicate. Significantly (P<0.05) higher weight gain was recorded in group Ph-250 at all recorded stages as compared to the control. Better Feed Conversion Ratio (FCR) was recorded in group Ph-250, followed by Ph-200 and Ph-300. Mean feed cost per chick was not affected by methanolic extract of P.harmala, however, numerically it was lowest for group Ph-250. Gross return per chick was significantly (P<0.05) higher in group Ph-250.The study showed that methanolic extract of P.harmala has improved the overall performance of broilers. The dose rate of 250 mg/L of drinking water has significantly improved the weight gain and gross return.
Keywords: Broilers; Peganum harmala; feed conversion ratio; feed cost; gross return.